PENINGKATAN KETERAMPILAN GURU SEKOLAH DASAR MENGGUNAKAN MEDIA INTERAKTIF UNTUK MATERI GEOMETRI DAN PECAHAN - Riry Sriningsih; Dewi Murni; Helma Helma (Pelita Eksakta, 2018)
Based on observations, questionnaires and discussions with some of teacher of elementary school found many problems geometric and fraction material. The problems are: 1. In general, teachers have not used interactive media in explaining mathematic materials, so students are difficult to understand the subject, 2. Teachers have not yet facilitated various learning styles of students, 3. Students' assumptions on difficult mathematical subjects (full of numbers and symbols), so they are phobic with math, 4. Teachers urgently need the consolidation of geometrical and fraction materials through the creation of interactive media that match the material and characteristics of students, 5. Teachers desperately need training on how to design and create interactive media that can interest students to learn on geometry and fraction materials, so that students are no longer fobs with math and can easily understand the material well, 6. Teachers desperately need training on the use / utilization of interactive media that has been created in teaching the geometry and fraction materials. To solve the problem, team try to provide solutions to these problems by providing training on how to design, create and use interactive media especially plane geometry and fraction. The result of training, teachers are already able to design and make interactive media. They can explain plane geometry and fraction material easily, especially how to find the formula of area for instance rectangle, triangle, trapezium, etc. Further impact, students more easily understand the material well.